Enantioselective synthesis of gamma-phenyl-gamma-amino vinyl phosphonates and sulfones and their application to the synthesis of novel highly potent antimalarials - Aratikatla, Eswar K.; Kalamuddin, Md; Malhotra, Pawan; Mohmmed, Asif; Bhattacharya, Asish K. (ACS Omega, 2020)
Racemic and enantioselective syntheses of gamma-phenyl-gamma-amino vinyl phosphonates and sulfones have been achieved using Horner-Wadsworth-Emmons olefination of trityl protected alpha-phenyl-alpha-amino aldehydes with tetraethyl methylenediphosphonate and diethyl ((phenylsulfonyl)methyl)phosphonate, respectively, without any racemization. The present strategy has also been successfully applied to the synthesis of peptidyl vinyl phosphonate and peptidyl vinyl sulfone derivatives as potential cysteine protease inhibitors of Chagas disease, K11002, with 100% de. The developed synthetic protocol was further utilized to synthesize hybrid molecules consisting of artemisinin as an inhibitor of major cysteine protease falcipain-2 present in the food vacuole of the malarial parasite. The synthesized artemisinin-dipeptidyl vinyl sulfone hybrid compounds showed effective in vitro inhibition of falcipain-2 and potent parasiticidal efficacies against Plasmodium falciparum in nanomolar ranges. Overall, the developed synthetic protocol could be effectively utilized to design cysteine protease inhibitors not only as novel antimalarial compounds but also to be involved in other life-threatening diseases.

Combating multi-drug resistant malaria parasite by inhibiting falcipain-2 and heme-polymerization: Artemisinin-peptidyl vinyl phosphonate hybrid molecules as new antimalarials - Aratikatla, Eswar K.; Kalamuddin, Md; Rana, Kalpeshkumar C.; Datta, Gaurav; Asad, Mohd; Sundararaman, Srividhya; Malhotra, Pawan; Mohmmed, Asif; Bhattacharya, Asish K. (European Journal of Medicinal Chemistry, 2021)
<span style="color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Artemisinin-based combination therapies (ACTs) have been able to reduce the clinical and pathological malaria cases in endemic areas around the globe. However, recent reports have shown a progressive decline in malaria parasite clearance in South-east Asia after ACT treatment, thus envisaging a need for new artemisinin (ART) derivatives and combinations. To address the emergence of drug resistance to current antimalarials, here we report the synthesis of artemisinin-peptidyl vinyl phosphonate hybrid molecules that show superior efficacy than artemisinin alone against chloroquine-resistant as well as multidrug-resistant Plasmodium falciparum strains with EC<span style="box-sizing: inherit; font-size: 12px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">50<span style="color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> in pico-molar ranges. Further, the compounds effectively inhibited the survival of ring-stage parasite for laboratory-adapted artemisinin-resistant parasite lines as compared to artemisinin. These hybrid molecules showed complete parasite clearance in vivo using P. berghei mouse malaria model in comparison to artemisinin alone. Studies on the mode of action of hybrid molecules suggested that these artemisinin-peptidyl vinyl phosphonate hybrid molecules possessed dual activities: inhibited falcipain-2 (FP-2) activity, a P. falciparum cysteine protease involved in hemoglobin degradation, and also blocked the hemozoin formation in the food-vacuole, a step earlier shown to be blocked by artemisinin. Since these hybrid molecules blocked multiple steps of a pathway and showed synergistic efficacies, we believe that these lead compounds can be developed as effective antimalarials to prevent the spread of resistance to current antimalarials.